WAYANG KULIT PARWA SEBAGAI MEDIA TRANSFORMASI NILAI AGAMA HINDU BAGI GENERASI MELENIAL (STUDI DESKRIPTIF PERTUNJUKKAN WAYANG KULIT LAKON PANDAWA AGURU DI GRIA PEREAN KEDIRI, TABANAN) - Ni Wayan Murniti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Effective strategies in delivering messages Hinduism teachings can be done with various media, one of which is Wayang Kulit media. The role of wayang kulit in conveying messages is quite effective because shadow puppets fulfill all the criteria of traditional media that can be used in communication, namely the form, theme, and flexibility of the media. The presence of Parwa’s shadow puppets art is still very popular with the people. Parwa Leather Puppets contain educational values such as: ethics, morals, and spirituality which are inserted in each chosen play, it makes art always interesting to witness. Of the several plays that are often performed are the Aguru Pandavas. Pandawa aguru is one of the plays that is dense with the contents of these educational values.Keywords: Parwa’s shadows puppets, transformation media, millennial generasi.